Analysis of the Internship Program "Merdeka Belajar Kampus Merdeka" Perspectives of Primary School Teachers’ Teaching Readiness - Muhamad Afandi; Sari Yustiana; Sri Wahyuningsih (Al Ibtida: Jurnal Pendidikan Guru MI, 2022)
AbstractThe purpose of this study is to analyze the “Merdeka Belajar Kampus Merdeka (MBKM)” program from the perspective of teachers’ teaching readiness. The study used a qualitative approach carried out at one elementary school in Wonosobo Regency, Central Java during the early days of learning activities from August to December 2021. Data were collected through observation, interviews, and questionnaires distributed to participants, which included teachers, students, and pre-service elementary school teachers of Universitas Islam Sultan Agung Semarang. Besides, the secondary data were obtained from books, journal articles, and other sources. The findings revealed that relating to teachers’ teaching readiness, there were 40% of educators mastered the concept of the MBKM program, while another 60% of them understood the term MBKM program from the existing information provided by media. In mastering Information and Communication Technology (ICT), 63% of educators stated that they had mastered ICT and were accustomed to using some social media for learning activities, while 37% of educators had not mastered ICT well but they only used ICT for certain purposes such as teaching the MBKM program although with a relatively low understanding.Keywords: merdeka belajar, internship program, teachers’ readiness, primary school. AbstrakTujuan dari penelitian ini adalah untuk menganalisis program merdeka belajar kampus merdeka (MBKM) dari perspektif kesiapan mengajar guru. Penelitian ini menggunakan pendekatan kualitatif yang dilaksanakan di salah satu sekolah dasar di Kabupaten Wonosobo, Jawa Tengah pada masa-masa awal kegiatan pembelajaran, yaitu Agustus-Desember 2021. Data diperoleh melalui observasi, wawancara, dan angket kepada partisipan yang meliputi guru, siswa, dan mahasiswa Universitas Islam Sultan Agung Semarang sebagai calon guru SD. Selain itu, data sekunder diperoleh dari buku, jurnal, dan sumber lainnya. Hasil temuan mengungkapkan bahwa terkait kesiapan guru dalam mengajar, terdapat 40% pendidik yang menguasai konsep program MBKM, sedangkan 60% lainnya hanya memahami istilah program MBKM dari media informasi yang ada. Dalam penguasaan Teknologi Informasi dan Komunikasi (TIK), 63% pendidik menyatakan telah menguasai TIK dan terbiasa menggunakan beberapa media sosial untuk kegiatan pembelajaran, sedangkan 37% pendidik belum menguasai TIK dengan baik, hanya menggunakan TIK untuk tujuan tertentu seperti mengajar dan berkomunikasi. Sehingga dapat disimpulkan bahwa para pendidik sudah siap mengajar dalam program MBKM meskipun dengan pemahaman yang relatif rendah.Kata kunci: merdeka belajar, program magang, kesiapan guru, sekolah dasar.